Analysis of Sanad and Matan in the Hadith on the Characteristics of Hypocrites: Study of Takhrij Hadith - Aini, Nuri Qurrotul; Shihab, Muhammad Fahmi (Journal of Takhrij Al-Hadith, 2025)
This study aims to discuss the sanad and matan of the Hadith and the characteristics of hypocrites. This research uses a qualitative approach with a descriptive-analytical method. The formal object of this research is hadith science. In contrast, the material object is the hadith about the characteristics of hypocrites in Sahih Muslim narration No. 90 Chapter of Faith in the Encyclopedia of Hadith. The study results explain that the Hadith narrated by Muslim No. 90 meets the requirements of sahih. Thus, this tradition can be used as a valid basis for discussing the signs of hypocrisy in Islam because it has a reliable sanad. This research is expected to contribute to studying hadith and Muslims’ understanding of avoiding hypocritical traits in daily life.